High temperature friction and wear experimental studies on 3D printed nickel iron base superalloy. (1st February 2023) - Tom, Ruben Jose; Thomas, Ciby; Venugopal, G.; Rajkumar, M.R.
In this paper, a nickel-base alloy is developed through 3D printing process following the laser sintering technique for high temperature wear application. The mechanical properties such as hardness, strength and density are evaluated to just the quality of 3D printed material. The Vickers hardness of the 3D printed nickel alloy is 265 Hv which is very close to the commercial alloy available superalloy in the market. The density of the 3D printed nickel alloy is 8.2 g/cc and for the conventional superalloy is 8.17 g/cc. From the sliding wear analysis, it has to be noticed that with respect to increase in load the coefficient of friction and wear rate found increasing gradually throughout the test duration. This is due to the frictional force and the working environment applied during the investigation. Mass loss is noticed at 10 N-150°C; to maximum of 0.306 g. The influence of thermal and mechanical load has influenced the contact surface damage.